The remains of the taboo: experiences, attitudes, and knowledge about menopause in the workplace. (3rd March 2020) - Beck, V.; Brewis, J.; Davies, A.
Abstract: Objectives: This study explored experiences of, attitudes to, and knowledge about menopause in the workplace among participants from the UK to assess the extent to which menopause remains a taboo in this context. Method: An online survey was distributed via Trades Union Congress, UK networks and social media, and was completed by 5399 respondents. Questions explored three key issues relating to menopause at work: respondents' own experiences of menopause transition; disclosure at work; and availability of information on menopause at work. Result: The largest group (43.4%) of respondents were perimenopausal and 16.8% were postmenopausal; 12.3% indicated that they might be experiencing menopause but were not sure. Only 45.8% had disclosed their menopause status at work. Fewer than 20% were provided with information about menopause in their workplace but the majority would like such information to be available. Conclusion: The survey findings suggest some progress has been made to raise awareness about menopause in the workplace but that substantial work remains to be done to ensure women transitioning through menopause are supported.